Pulmonary Alveolar Proteinosis Due to Pneumocystis carinii in Type 1 Hyper-IgM Syndrome: A Case Report - Zhang, Fei Zhou; Yuan, Jie Xin; Qin, Lu; Tang, Lan Fang (Frontiers in Pediatrics, 2020)
Background: Pulmonary alveolar proteinosis (PAP) is a rare diffuse lung disease. Reports of rare cases of PAP due to Pneumocystis carinii (P. carinii) exist in infants with immunodeficiency diseases, but no cases have been reported till date in pediatric patients with type 1 hyper-IgM syndrome (HIGM1). Case presentation: Herein, we present a case of PAP secondary to P. carinii in an infant with HIGM1. He was admitted to our unit because of cough and tachypnea. Lung biopsy confirmed the diagnosis of PAP, whereas hexamine-silver staining of the bronchoalveolar lavage fluid identified P. carinii infection. No other probable cause of PAP was observed. Whole exome sequencing indicated a novel c.511dupA (p.I171N*30) hemizygous mutation in the CD40 ligand (CD40LG) gene. He was cured with bronchoalveolar lavage and compound sulfamethoxazole tablets. Conclusions: To our knowledge, this is the first reported case of P. carinii as a reversible cause of PAP in an infant with HIGM1.